LA BIOLOGIA SINTETICA COME UN NUOVO QUADRO INTERPRETATIVO DEI SISTEMI VIVENTI (Istituto Lombardo - Accademia di Scienze e Lettere - Rendiconti di Scienze, 2014)
Synthetic Biology is not just a contemporary update of the recombinant DNA technologies of the past 30 years along with a descriptive language imported from electrical and industrial engineering. It is also a new interpretative key of living systems as well as a declaration of intent on the use and reprogramming of biological objects for human benefit. In the same way that scientific chemistry initiated by Lavoisier evolved into the Chemical Engineering that is the basis of our industrial society, Biology has acquired a transforming potential that will possibly lead to a type of industry and economy very different from the current paradigm. To this end, it is essential to identify bottlenecks that limit the design of biological objects from first principles and not to miss the train of Synthetic Biology at its current foundational stage, when talent -and not the muscle- is what really matters.